TRANSFORMASI MEDIA TRADISIONAL: KEUNTUNGAN MENGGUNAKAN FLIPBOOK DIGITAL DALAM PEMBELAJARAN DI SEKOLAH DASAR - Afifah Dwi Rahmadhani; Nurhafizah lubis; Abdullah Taufik Ritonga; Nunu Mahnun (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The transformation of learning media from paper and statistical presentations to digital interactive formats has become an important part of efforts to improve mutual teaching and student engagement. One form of innovation that has emerged is the digital flipbook. This study aims to examine the advantages or positive impacts of using flipbooks in learning through a systematic literature review approach with the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) method. The search strategy was carried out through databases such as Google Scholar, Scopus, and ScienceDirect with the keywords